2016
DOI: 10.3163/1536-5050.104.3.004
|View full text |Cite
|
Sign up to set email alerts
|

Instructional methods used by health sciences librarians to teach evidence-based practice (EBP): a systematic review

Abstract: Background: Librarians often teach evidence-based practice (EBP) within health sciences curricula. It is not known what teaching methods are most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Another reason health sciences librarians may not appreciate the applicability of the Framework could include the constraints of typical health sciences librarian instructional efforts. In a recent systematic review of instructional methods that health sciences librarians used to teach EBP [ 15 ], nearly all of the included studies had clinician or researcher coauthors, suggesting librarians often work with teams of faculty to integrate EBP. The compromises required when working in a faculty team where curricula are already crowded may limit health sciences librarians’ abilities to significantly change their approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason health sciences librarians may not appreciate the applicability of the Framework could include the constraints of typical health sciences librarian instructional efforts. In a recent systematic review of instructional methods that health sciences librarians used to teach EBP [ 15 ], nearly all of the included studies had clinician or researcher coauthors, suggesting librarians often work with teams of faculty to integrate EBP. The compromises required when working in a faculty team where curricula are already crowded may limit health sciences librarians’ abilities to significantly change their approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature on teaching evidence-based decision making conducted by Swanberg et al found that the majority of health sciences institutions teach it in the lecture format. 2 Indeed, teacher-centered lectures still prevail in U.S. health sciences institutions. [3][4][5][6] This instructional approach poses challenges to instructors and students.…”
mentioning
confidence: 99%
“…Many curricula for the education of health professionals now include evidence‐based practice. This follows national recommendations and fulfils accreditation requirements (Swanberg et al , ). There is also a strong emphasis in pre‐ and post‐registration preparation of nurses on knowledge of research methods; however, there is not an explicit focus on the practical application of research processes to control data quality and reliability and ensure ethical conduct.…”
Section: Suggestions For Futurementioning
confidence: 76%